Next of kin - Schulze, Klaus 1947-2022 (Severin Films, 2019)
"Linda Stevens has just inherited Montclare, a retirement home left to her by her late mother. When she finds her mother's diary she reads tales of mysterious events within the house - taps turning themselves on and off, candles lighting and voices in the night. When history begins to repeat itself Linda's nightmares are just the beginning. Montclare hides a dark secret and she is soon fighting for her life." [amazon.de]